From Art to Social Entrepreneurship Praxis: The Collaboration Dynamics of Warung Murakabi Minggir through Interpretative Phenomenological Analysis - Pradinasari, Ryanda Khansa; Pratikno, Heri; Sopiah, Sopiah (PT. Riset Press International, 2023)
In this article, we delve into the collaboration dynamics of Warung Murakabi Minggir, a social entrepreneurship praxis of collaboration that uniquely merges art, locality, and mutual cooperation to tackle social issues. The purpose of this research is to understand how the participants make sense of their collaborative experiences in Warung Murakabi Minggir. Our study employs Interpretative Phenomenological Analysis (IPA) to delve into the lived experiences and viewpoints of the individuals engaged in the collaboration. This article sheds light on the critical role of collaboration within diversity in establishing sustainable social entrepreneurship practices. The findings of our study emphasize a deep comprehension of how collaborative experiences in Warung Murakabi Minggir serve as catalysts for generating positive social impact. Moreover, the research emphasizes the pivotal role of collaboration, how the dynamics of collaboration can either facilitate or impede progress of Murakabi Minggir as social entrepreneurship praxis